PP.42.19: THE ROLE OF GASOTRANSMITTERS IN REGULATING OF THE FUNCTIONS OF SMOOTH MUSCLES. (June 2015) - Kovalev, I.; Gusakova, S.; Smagliy, L.; Birulina, J.; Idamgapova, T.; Nosarev, A.; Medvedev, M.; Orlov, S.
Abstract : Objective: Gasotransmitters (NO, H2S, CO) and traditional messengers (calcium, cyclic nucleotides, the products of phosphoinositides and proten kinase C) participate in the mechanisms of regulation of contractile function of smooth muscle cells (SMCs). Since nitric oxide (NO), considered relaxing effects of gasotransmitters, but remain questions about the membrane and molecular targets of the actions of their effects. Design and method: Influence of carbon monoxide (CO) and hydrogen sulfide (H2S) on the electrical and contractile activities of smooth muscle cells of the guinea pig ureter and rat aorta were studied by methods of double sucrose bridge and mechanography. Results: It has been shown that CO donor (CORM II) causes a dose-dependent decrease of the contractile response of SMCs of the ureter and rat aorta and also reduces the amplitude and duration of the action potential plateau. The inhibitory effect of CO is attenuated by blocking potassium channels of SMCs with tetraethylammonium (TEA) or inhibition of soluble guanylate cyclase (ODQ [1H- [1, 2, 4] -oxadiazolo [4, 3-a] quinoxalin-l- one]). In experiments with a donor of hydrogen sulfide (NaHS), it was shown, that it has an activating effect on the electrical and contractile activities of SMCs of the guinea pig ureter, which is caused by the action of potassium conductivity of the membrane. Activating effect of H2S decreased by blocking ATP-dependent channels with glibenclamide. Analysis of the effect of H2S on sodium and calcium conductance of the membrane smooth muscles of the ureter using modified sodium-free and TEA-containing Krebs solution showed that the contribution of potassium conductance is mainly sold at high concentrations (100 and 1000 μmol) donor NaHS. Probably, that the impact of low concentrations of NaHS on the amplitude of contractions SMCs of the ureter and performed through the activation of the calcium component of the action potential. Conclusions: Thus, the effects of carbon monoxide on the electrical and contractile activities of SMCs are associated with an increase potassium conductivity of the membrane or the activation of soluble guanylate cyclase. Activating effect of NaHS determined by involving sodium-dependent ion transporters to inhibition of potassium conductance of smooth muscles.